Urban Community Participation In Dealing With The Covid-19 Pandemic Through Environment-Based On Covid-19 Handling Policies In The City Of Mataram - Diki Wahyudi; Sri Rum Giyarsih; Dina Ruslanjari; Sukron Azhari (ASTEEC, 2023)
The city of Mataram is an area that has a high number of Covid-19 cases in West Nusa Tenggara Province. Covid-19 has seriously impacted all aspects of life, from health, economy, society, culture, and tourism to religious rituals. This study aims to analyze the policies for handling Covid-19 in Mataram City. Second, analyze the form of community participation in efforts to deal with Covid-19 in Mataram City. This study uses the participation theory of Cohen and Uphoff as an analytical tool. This research is qualitative research with a descriptive approach. In- depth interviews, observation, and documentation employed data collection techniques. The results of this study indicate that this environment-based policy for handling Covid-19 effectively suppresses the spread of Covid-19 in Mataram City. This policy is implemented by involving the participation of all elements of government, local leaders, and the community. Community participation in handling Covid-19 starts with high public awareness of Covid-19, then implementing health protocols. Community participation is also seen in the formulation of policies for handling Covid-19, the movement to join a Task Force (Satgas), carrying out self- help movements to help each other, and being involved in evaluating the handling of Covid-19 in the City of Mataram.